PENGGUNAAN DAN PERGESERAN BAHASA MASYARAKAT BELU DI KECAMATAN TASIFETO TIMUR (The Language Use and Language Shift of Belu Community at The East Tasifeto Districts) - Dewi Nastiti Lestariningsih (Kandai, 2017)
The result presented in this paper is the result of a survey conducted by Subbidang Tenaga Kebahasaan, Bidang Pembelajaran, Pusat Pembinaan, Badan Pengembangan dan Pembinaan Bahasa in 2016. In general, the survey aims to provide an overview of the language situation that includes language attitude also a description of the use of Indonesian, local languages, and foreign languages in the border region of the NTT and Timor Leste. The survey on the use of the Indonesian language, local languages, and foreign languages is done by quantitative and qualitative methods based on a questionnaire of language use and language attitude. In general, language speakers in the district of Belu admit that their attitude show loyalty to the Indonesian. Based on the results of research, the Indonesian language use has been done in the formal situastion and public space. Another interesting thing that we have found in the language use is the language shift from local languages to Indonesian language. This is shown by the use of Indonesian language by the respondents (productive age) when communicating to their children at home. The factors influencing language shift due to social factors. The handling efforts tend to be the local language learning at home and the elementary level in school.